Neotropical migratory and resident birds occurring in sympatry during winter have distinct haemosporidian parasite assemblages. (17th December 2019) - Soares, Leticia; Latta, Steven C.; Ricklefs, Robert E.
Abstract: Aim: We compared the parasite assemblages of over‐wintering migratory birds and permanent residents on the wintering grounds. We determined whether parasite sharing between migratory and resident birds is influenced by host phylogenetic relatedness. We then inferred whether migratory birds transport haemosporidian parasite lineages between the breeding and wintering grounds. Location: Sierra de Bahoruco National Park, Dominican Republic, Hispaniola. Taxa: Migratory and resident birds (primarily Aves: Passeriformes) and their haemosporidian parasites (order Haemosporida, Plasmodium, Haemoproteus and Parahaemoproteus ). Methods: We used mist nets to capture birds in thorn scrub, broadleaf dry forests and pine forests during midwinter. We used molecular methods to recognize haemosporidian parasites in blood samples, and genotyped infections based on the nucleotide differences in a region of the parasite cytochrome b gene. Results and Main Conclusion: We identified 505 infections by 32 haemosporidian parasite lineages in 1, 780 blood samples from 37 resident species, and in 901 blood samples from 14 overwintering migratory species, over five years at the same sites. Infection prevalence varied among migratory species from zero to 13%, whereas infection prevalence among resident species ranged up to 77%. Host relatedness did not predict parasite assemblage similarity. We discuss four hypotheses for the rarity of haemosporidian infections in migratory birds during winter, and for the infrequency of parasite sharing between migratory and resident birds: (a) relative abundance and host preferences of dipteran vectors lower parasite transmission to migratory birds; (b) parasite lineages adapted to infect endemic Caribbean hosts are unable to infect migratory species; (c) the physiology of migratory birds after migration and during winter reduces parasite survival; and (d) infected individuals suffer more pronounced mortality rates during migration. We highlight the link between host–parasite coevolution and the physiological adaptations associated with avian seasonal migration.